Coarctation of Aorta (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Coarctation derived from Latin term coartatio, which translated literally means a drawing together. When used in the context of congenital heart disease, Coarctation refers to an area of narrowing of the thoracic aorta in the region of the insertion of arterial duct, with or without additional abnormalities of the aortic arch.Aortic Coarctation accounts for 6-8% life births with congenital heart disease. Coarctation occurs more commonly in males, with a male: female ratio ranging from 1.27 to 1.74.DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i1.19422